Sociologies of poetry translation emerging perspectives - Blakesley, Jacob 1978- (Bloomsbury Academic, 2019)
"While the sociology of literary translation is by now well-established, and even flourishing, the same cannot be said specifically for the sociology of poetry translation. This volume, the first to address poetry translation using a variety of sociological and socio-political approaches, showcases poetry translation looked at from the distinctive perspectives offered by theorists like Pierre Bourdieu and Niklas Luhmann. Discussing poetry translated from and/or into a variety of languages, such as Catalan, Czech, English, Irish, Italian, Russian, Slovakian, Spanish, Swahili, Swedish, and Ukrainian, Sociologies of Poetry Translation addresses poetry translation from sociological perspectives in order to catalyse new methods of investigating poetry translation and features new research on how ideological stances and historical movements affect it. Making the case for a move from the singular 'sociology of poetry translation' to the pluralist 'sociologies', this book accounts for the rich variety of approaches that are currently emerging to deal with poetry translation"
Includes bibliographical references and index
Keywords: Poetry -- Translating; Translating and interpreting -- Social aspects; Übersetzung; Soziologie; Übersetzer; Lyrik; Aufsatzsammlung